Liquid Biopsy - Strumfa, Ilze; Gardovskis, Janis (IntechOpen, 2019)
Reliable diagnosis is the cornerstone, starting point, and prerequisite of successful treatment. Therefore, development of innovative diagnostic technologies represents a hot topic in medical research. Liquid biopsy is a novel, minimally invasive laboratory evaluation concept for diagnostic, prognostic, and predictive testing, as well as dynamic monitoring of treatment or disease course. To achieve these goals, a multitude of specific, targeted tests can be performed to detect free nucleic acids, exosomes, microRNAs, tumor-educated platelets, and whole cells of tumor or fetal origin in different biological fluids, including blood, urine, cerebrospinal fluid, and others. Although tissue biopsy has long been considered the gold standard of diagnostics, especially regarding malignant tumors, liquid biopsy has the advantages of a non-invasive approach and thus low risk of complications. It is technically feasible even in serious general status or if tumors or metastases are not easily accessible using conventional tissue biopsy. The testing is fast, exact, and can be repeated to ensure real-time follow-up. In contrast to classic tumor markers, liquid biopsy is distinguished by high specificity at genomic, proteomic, and cellular levels. It is expected to equal and exceed the diagnostic value of tissue biopsy. The field of liquid biopsies is developing rapidly regarding the selection of targets, technological improvements, and quality assessment. This book, written by a global team of recognized scientists, comprises state-of-the-art reviews on the current knowledge and advances in the technologies and software for liquid biopsy. Examples of practical application of liquid biopsy to evaluate thyroid cancer, multiple myeloma, etc. are discussed as well. The book is intended to serve as a reference for scientists and clinicians interested in the development and practical implementation of liquid biopsy.